A rare case of term viable abdominal pregnancy - Chaudhary, Aarushi; Antil, Sarvottma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Abdominal pregnancy is a rare event, but the one that represents a grave risk to the health of the pregnant woman. An abdominal pregnancy is defined as an ectopic pregnancy that implants in the peritoneal cavity. Advanced abdominal pregnancy is a rare event with high fetal and maternal morbidity and mortality. Abdominal pregnancy is exclusive of tubal, ovarian or intra-ligamentary pregnancy. Few cases have been reported in literature so far. Here is a case of undiagnosed abdominal pregnancy surviving up to term with successful fetomaternal outcome, complications encountered during its management, role of ultrasound and MRI for same.